Bleeding Risk With Combining Antiplatelets and Anticoagulants for Secondary Stroke Prevention: A Propensity Score–Matched Analysis - Farrokh, Salia; Nalleballe, Krishna; Onteddu, Sanjeeva; Suarez, Jose I.; Bösel, Julian; Shah, Vishank A. (Journal of the American Heart Association, 2025)
Limited data exist on the safety of combining antiplatelets and anticoagulants for secondary stroke prevention in acute ischemic stroke (AIS). We sought to examine the hemorrhage risk with combining single (SAPT) or dual antiplatelet therapy (DAPT) with anticoagulants in patients with AIS with concomitant atrial fibrillation and acute myocardial infarction. This retrospective cross-sectional cohort study used TriNetX to collect data from 76 hospitals in the United States. Adult patients with diagnoses of AIS, atrial fibrillation, and acute myocardial infarction were identified using , ( ) codes. Propensity score-matched analysis, compared the odds for acute spontaneous intracerebral hemorrhage and gastrointestinal bleeding at 3 months, 12 months, and throughout follow-up within TriNetX, among 3 matched subcohorts: anticoagulant alone, anticoagulant plus SAPT, and anticoagulant plus DAPT. Among 144 434 patients with AIS, atrial fibrillation, and myocardial infarction (mean age, 71.9 years; 43.3% women), 8772 (6.1%) patients received anticoagulants alone, 88 430 (61.2%) received anticoagulant plus SAPT, and 47 232 (32.7%) received anticoagulants plus DAPT. After propensity score matching, 8706 patients were included in each subcohort. Compared with anticoagulant alone, anticoagulant plus SAPT and anticoagulant plus DAPT showed no significant increase in intracerebral hemorrhage risk at 3 and 12 months but increased long-term risk (odds ratio for anticoagulant plus SAPT, 1.26 [95% CI, 1.11-1.44], <0.001; for anticoagulant plus DAPT, odds ratio, 1.34 [95% CI, 1.18-1.53]; <0.001). Gastrointestinal bleeding risk was elevated at all time points with combination therapies. Combining antiplatelets with anticoagulants after AIS may be associated an increased risk of intracerebral hemorrhage in the long term, particularly beyond 12 months, but with an increased risk of acute gastrointestinal bleeding in the short and long term. Larger prospective studies are warranted to confirm our findings.